2021
DOI: 10.1021/acs.jpcc.1c07681
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical CO2 Reduction Reaction on 3d Transition Metal Single-Atom Catalysts Supported on Graphdiyne: A DFT Study

Abstract: In the electrochemical CO2 reduction reaction (CO2RR), single atom catalysts (SACs) supported on carbon materials have exhibited high activity and selectivity. However, the carbon supports are mainly graphene and carbon nanotubes, which are composed of sp2-hybridized carbon. Graphdiyne with sp-hybridization has been investigated as a promising carbon material for various catalytic reactions. In this study, the effect of sp-hybridization on graphdiyne was investigated using density functional theoretical (DFT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The electroreduction of carbon dioxide has become one of the critical technologies of the clean energy economy, holding promise to reduce and mitigate the carbon footprint resulting from the use of chemicals and fuels. Understanding the CO 2 reduction reaction (CO 2 RR) mechanism at the atomic level is instrumental for catalyst design and catalytic system’s optimization. Theoretical approaches are promising for studying reaction mechanisms of various electrochemical reactions, including CO 2 electroreductions. CO 2 RR on Au surfaces is of great interest to convert CO 2 to the valuable chemical (CO, a critical component of syngas). , So far, many simulations performed at solid–gas interfaces using density functional theory (DFT) focus on the thermodynamics of reaction intermediates without considering reaction kinetics. Such simplified models are insufficient to capture interfacial behaviors and evaluate atomic-scale mechanisms of electrocatalytic reactions at complex electrode–electrolyte interfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…The electroreduction of carbon dioxide has become one of the critical technologies of the clean energy economy, holding promise to reduce and mitigate the carbon footprint resulting from the use of chemicals and fuels. Understanding the CO 2 reduction reaction (CO 2 RR) mechanism at the atomic level is instrumental for catalyst design and catalytic system’s optimization. Theoretical approaches are promising for studying reaction mechanisms of various electrochemical reactions, including CO 2 electroreductions. CO 2 RR on Au surfaces is of great interest to convert CO 2 to the valuable chemical (CO, a critical component of syngas). , So far, many simulations performed at solid–gas interfaces using density functional theory (DFT) focus on the thermodynamics of reaction intermediates without considering reaction kinetics. Such simplified models are insufficient to capture interfacial behaviors and evaluate atomic-scale mechanisms of electrocatalytic reactions at complex electrode–electrolyte interfaces. , …”
Section: Introductionmentioning
confidence: 99%
“…8b and c. For HCOOH generation, the U L on Mn/Fe/Ni-pyGYs is lower than those of many CO 2 RR electrocatalysts, such as Ni/Co/Fe-C 3 N 4 (À0.77 to À1.09 V), 44 Mn/Ni/Cugraphdiyne (À0.45 to À0.64 V), 45 and metal porphyrin (M-PP) sheets (À0.52 to À1.06 V), 30 as shown in Fig. 8b.…”
Section: Performances Of Tm-pygysmentioning
confidence: 92%
“…Meanwhile, Bao's team utilized DFT to systematically investigate the effect of Mn, Fe, Co, Ni, Cu, and Zn single-atom catalysts (SACs) on CO 2 RR to methanol using graphdiyne carriers (M-graphdiyne), which effectively inhibited HER competition. [96] The significant orbital hybridization and delocalized charge distribution indicated that sp-hybridized actively participates in changing the electronic structure of metal atoms. The free energy diagram obtained by DFT showed that the energy barrier of Co-graphdiyne was only 0.3 eV, which was more active than other SACs and indicated high selectivity for reducing CO 2 to CH 3 OH (Figure 3e).…”
Section: Dft Calculations For Co 2 Rr Investigationmentioning
confidence: 99%